2010
DOI: 10.1177/0305735610373602
|View full text |Cite
|
Sign up to set email alerts
|

Does timbre affect pitch?: Estimations by musicians and non-musicians

Abstract: The present article focuses on the question of whether the timbre difference of two sounds with harmonic spectra, produced by natural musical instruments or the singing voice, may influence subjective assessments of the pitch of one sound in relation to the pitch of the other. The authors administered a series of perception tests to a group of professional musicians (n = 13) and a group of non-musicians (n = 13). The tests used the following pre-recorded sounds: the singing voice, the sound of the viola, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 17 publications
0
32
0
2
Order By: Relevance
“…This was also confirmed in an experiment by Schubert and Wolfe (2006) in which they found that perceptual brightness was influenced by the pitch. Similarly, the perception of pitch may change with timbre (e.g., Vurma et al, 2011). This confirms an interaction effect but will not explain the large correlation found in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 41%
“…This was also confirmed in an experiment by Schubert and Wolfe (2006) in which they found that perceptual brightness was influenced by the pitch. Similarly, the perception of pitch may change with timbre (e.g., Vurma et al, 2011). This confirms an interaction effect but will not explain the large correlation found in this study.…”
Section: Conclusion and Discussionmentioning
confidence: 41%
“…Concerning the perceptual process, several studies reported that spectral composition (Hutchins et al, 2012;Russo & Thompson, 2005;Vurma et al, 2010;Warrier & Zatorre, 2002) and vibrato (van Besouw et al, 2008) affect the perception of tones. The several interactions observed in our multiple regression modeling showed that the individual acoustical parameters cannot be observed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pitch perception of tones differs depending on spectral composition (Hutchins, Roquet, & Peretz, 2012;Russo & Thompson, 2005;Vurma, Raju, & Kuuda, 2010;Warrier &Zatorre, 2002) andvibrato (van Besouw, Brereton, &Howard, 2008). As the evaluation of performed pitch intervals is based on the pitch level of individual notes and the perception of tones is altered by the acoustical components involved (and appreciated) in operatic singing voices, it may be particularly complex to evaluate such voices.…”
mentioning
confidence: 99%
“…Second, the definition of pitch accuracy in operatic singing voices is based on the interaction of several parameters (Larrouy-Maestri et al, 2014a), in contrast with the definition of pitch accuracy of melodies performed by occasional singers (Larrouy-Maestri, Lévêque, Schön, Giovanni, & Morsomme, 2013;Larrouy-Maestri et al, 2015). In addition, parameters such as the spectral composition of the sound (e.g., Hutchins, Roquet, & Peretz, 2012;Russo & Thompson, 2005;Vurma, Raju, Kuuda, 2010;Warrier & Zatorre, 2002) or vibrato (van Besouw, Brereton, & Howard, 2008) influence pitch perception. The combination of these parameters in a single signal may enhance the complexity of the task for laypersons and challenge their perceptual abilities, which are typically deemed weaker than music experts' (e.g., Kraus & Chandrasekaran, 2010;Micheyl, Delhommeau, Perrot, & Oxenham, 2006;Schellenberg & Weiss, 2013;Tervaniemi, Just, Koelsch, Widmann, & Schroger, 2005;Varnet, Wang, Peter, Meunier, & Hoen, 2015; but see Larrouy-Maestri et al, 2015;Vanden Bosch der Nederlanden, Hannon, & Snyder, 2015, for contradictory findings).…”
mentioning
confidence: 99%